2021
DOI: 10.3390/ijerph182312360
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Literature on Dental Caries and Periodontal Disease in Socio-Economically Disadvantaged Individuals

Abstract: Dental caries and periodontal disease represent a health problem and a social cost for the entire population, and in particular for socio-economically disadvantaged individuals who are less resistant to disease. The aim of this review is to estimate the prevalence and severity of the two dental pathologies, caries and periodontal disease, in the different classes of socio-economically disadvantaged subjects and to understand which of them are most affected. A systematic search of the literature was performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 212 publications
(394 reference statements)
1
14
0
1
Order By: Relevance
“…High alcohol intake is associated with an increased risk of developing oral cancer or other potentially malignant disorders, periodontitis, dental caries, and xerostomia. Poor oral hygiene can lead to the development of dental caries and periodontitis, and is also associated with heart disease, cancer, and diabetes [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…High alcohol intake is associated with an increased risk of developing oral cancer or other potentially malignant disorders, periodontitis, dental caries, and xerostomia. Poor oral hygiene can lead to the development of dental caries and periodontitis, and is also associated with heart disease, cancer, and diabetes [ 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, most researchers tend to explore the relationship between socio-economic and prevalence of oral diseases. For instance, a systemic review found those in disadvantaged socio-economic status were more susceptible to PD because they had less access to dental care [32]. Several studies have already shown the necessity and social value of covering dental care benefits in healthcare insurance schemes [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive surgery is preferred as far as possible, the blood supply of alveolar bone plate is preserved, and the biological type of gingiva is changed as far as possible through soft tissue increment. [16] (2) Restoration: Patients with periodontal disease are limited by the interference of residual natural teeth, anatomical factors and the reduction of vertical bone height in the mouth, which can significantly improve the difficulty of restoration. In order to ensure good restore effect, the following factors need to be fully considered: ①Self-cleaning: Compared with those without a history of periodontitis, patients with periodontitis are more susceptible to implant inflammation after treatment.…”
Section: Overview Of Aesthetics and Restorationmentioning
confidence: 99%